Expert System Diagnoses Kidney Failure In Hemodialysis Patients Using Forward Chaining Methods - Susanti, Eka; Simanjorang, R. Mahdalena (Sean Institute, 2023)
Technological advances, one of which is in the health sector, which is needed to find out the available information, one of which is the diagnosis of kidney failure. The purpose of this study is to be able to find out kidney failure experienced by patients easily without having to manually diagnose and be able to build an expert system application on kidney failure with the Forward Chaining method and produce high accuracy values ​​and provide solutions for every disease experienced by the patient. The development of an expert system uses a research methodology consisting of problem analysis, data collection, data analysis, application of forward chaining methods, system design, system testing and system implementation. The Forward chaining method in the test resulted in an accuracy value of 70% with symptoms fulfilled with the description of Chronic Kidney Failure, so that the treatment solution that can be done is to live a healthy lifestyle by avoiding conditions that can trigger chronic kidney failure. How to treat chronic kidney failure is by giving drugs, dialysis (hemodialysis) and kidney transplantation.